A Survey-Evaluation of the Nutritional Habits among Students - Ismail, Y.; Kumar , V. Vijaya (Recent Updates in Disease and Health Research Vol. 8, 2024)
Nutrition refers to the quality and quantity of diet consumed in accordance with the nutritive value of the body. A healthy diet is an appropriate diet that is required to maintain physical and mental activity. It is an essential component of optimal health. Nutrition education has a significant impact on public consciousness and, as a result, society's health. Nutritional and healthy diet awareness programmes will assist the public in eating a balanced diet. Some researchers found that most of the students are not aware of healthy foods, which are essential to our body's functioning. The present survey is aimed to evaluate the nutritional habits of the students. The survey was conducted on the various college students (300 subjects) who have aged between 17-22 years by using a self-administered questionnaire. The questionnaire was mainly related to their nutritional habits like how often they avoid meals, how often they consume a portion of fresh fruits and vegetables, and how much fat. 300 subjects in total were involved in the study, among them 195(65%) were females and 105(35%) were males. It was observed that 112 (37.33%) skipped their breakfast, 65(21.66%) skipped their Lunch and 123(41.00%) skipped their dinner. According to O’Dea in 2005, avoiding of meals specifically breakfast disturbs the body’s metabolism and leads to diabetes. In this study, 245(81.66%) of subjects usually eat different kinds of vegetables but few students 55(18.33%) among them eat fruits each week. A majority of 231(77.00%) students opted for a high-fat diet.